Influence of site preferences on structural and magnetic properties of Cr-Sn substituted SrAl4Fe8O19 hexa-ferrite, an improved ceramic permanent magnet - Shekhawat D.; Prajapati S.; Roy P.K. (My University, 2025)
Chromium and tin substituted strontium hexaferrites {SrAl4(Cr0.5Sn0.5)xFe8 - xO19 with x = 0.0, 0.2, 0.4, 0.6, and 0.8} were synthesized by the sol-gel auto-combustion route. Rietveld refinement of X-ray Diffraction patterns was performed to reveal the phase purity, crystal structure, and unit cell parameters, such as lattice constants, bond angles, and bond lengths. Types of bonds were also verified using Fourier Transform Infrared Spectroscopy. Scanning Electron Microscope was used to explore the effect of substitution on the microstructure. Furthermore, the effect of Cr+3 and Sn+4 substitution on magnetic properties was studied using the Magnetic Property Measurement System. The relationship among the allocation of cations over the 5 sublattices of Fe+3 with substitutions was also analyzed. The saturation magnetization and magnetocrystalline anisotropy were calculated by the "Law of Approach to Saturation magnetization (Ms)" technique at room temperature. The maximum Br and (BH)max was theoretically calculated about 7.62 kG and 7.60 MGOe, respectively, for x = 0.60 composition. Cr-Sn substituted Sr-hexaferrite can be proposed for applications as a permanent magnet with a good deal of consistency. © 2019 Author(s).